Automatic reconstruction of the luminal carotid bifurcation axis using transverse ultrasound images - Catarina F. Castro (2019)
Feature and structure identification in medical images allows a faster identification of certain anomalies and diseases. The study presented here enables the automatic reconstruction of the arterial bifurcation lumen axis using carotid B-mode ultrasound images. The segmentation methodology introduces new indexes in the automatic process aiming better accuracy in the selection of the correct artery structure as compared to previously published developments.